Health and cleanliness : a text book for teachers - Green, George H. (George Henry), 1881- ; Buchan, G. F.; Muir, W. A. (London : Health and Cleanliness Council)
1938-03 1938 1930s 69 pages : illustrations HEALTH . AND . CLEANLINESS A . TEXT . BOOK . FOR . TEACHERS [Logo] Where there's dirt There's danger LONDON HEALTH . AND . CLEANLINESS . COUNCIL 177/5/8/3